2016
DOI: 10.1002/chem.201604995
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis for the Asymmetric [3+2] Cycloaddition of Vinyl Aziridines with α,β‐Unsaturated Aldehydes

Abstract: The first asymmetric [3+2] cycloaddition of vinyl aziridines with α,β-unsaturated aldehydes, based on synergistic catalysis, is disclosed. This methodology allows the formation of attractive pyrrolidine structures in good yields (up to 84 %), moderate diastereoselectivity, and high enantioselectivity values (up to >99 % ee). Additionally, a tricyclic pyrrolidine core structure found in biologically active molecules was synthesized in a one-pot fashion by using the presented reaction concept. Finally, a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…The fused polycyclic pyrrolidine skeletons are privileged structural motifs that are frequently encountered in biologically active natural products, with significant applications in the pharmaceutical and biological community . Among them, the tricyclic pyrrolidine motif is the key structural moiety in alkaloids and biologically active compounds, such as Rivastigmine analogs which exhibit the significant inhibitory effects on acetylcholinesterase, as well as, the tricyclic pyrrolidine display biological activity, for example, dipeptidyl peptidase IV (DPP‐4) inhibitors, was identified . As a result, the development of efficient methods for the construction of such frameworks have triggered increasing interest in organic and medicinal chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…The fused polycyclic pyrrolidine skeletons are privileged structural motifs that are frequently encountered in biologically active natural products, with significant applications in the pharmaceutical and biological community . Among them, the tricyclic pyrrolidine motif is the key structural moiety in alkaloids and biologically active compounds, such as Rivastigmine analogs which exhibit the significant inhibitory effects on acetylcholinesterase, as well as, the tricyclic pyrrolidine display biological activity, for example, dipeptidyl peptidase IV (DPP‐4) inhibitors, was identified . As a result, the development of efficient methods for the construction of such frameworks have triggered increasing interest in organic and medicinal chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Michelet, 5 Jørgensen, 6 Wei Wang 7 and Rios 8 reported a formal ring expansion of vinyl cyclopropanes with enals for the formation of spiro compounds under Pd(0) and secondary amine catalysis. Later on, Jørgensen reported vinyl aziridine opening 9 and [4 + 2] decarboxylation 10 ( Scheme 1 top) using a synergistic approach with excellent results. Rios' group has been one of the pioneers in the use of synergistic catalysis merging transition metal catalysts/metal Lewis acid and amine catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Since Yamamoto and co-workersr eported the seminal study of the Pd-catalyzed [3+ +2] cycloaddition of vinyl aziridines and electron-deficient alkenes for the formation of pyrrolidines in 2002, [3] several significant achievements have appeared. [3][4][5][6][7][8][9][10] Knight adopted 5-vinyloxazolidinones as the equivalent of vinyl aziridines through decarboxylation, [4] and Ooi group provided first example of asymmetric version of the reaction. [5] In both cases highly active double-activated alkenes were needed; [3][4][5][6] however,A ggarwal revealed that the use of mono-activated alkenes as reactants were prossible, [7] ando ur group realized the enantioselective cycloaddition reactiono f vinyl aziridines with a,b-unsaturated ketones.…”
mentioning
confidence: 99%
“…[9] Very recently,J ørgensen group reportedt he asymmetric [ 3 + +2] cycloaddition of vinyl aziridines with a,b-unsaturated aldehydes based on synergistic catalysis. [10] In spite of these progresses, the Michael acceptors were only those electron-deficient alkenes, and the enantioselective version of the reactions is also limited. To develop an ew type of Michael acceptor for the enantioselective [3+ +2] cycloaddition is highly valuable.…”
mentioning
confidence: 99%
See 1 more Smart Citation